Auditoria regular realizada a las instituciones educativas Antonio Nariño, Baudelio Montoya, General Santander, Instituto Calarcá, Instituto Tecnológico, Jesús María Morales y San José del municipio de Calarcá vigencia 2012 (2013)
The audit Regular on Educational Institutions “Antonio Nariño, Baudilio Montoya, General Santander, Instituto Calarcá, Instituto Tecnológico, Jesús María Morales and San José” located in Calarcá city according to Rendered information effect in 2012. It was executed according to the parameters established in the New Audit Guide for Territorial entities were adopted by the General controllership of Quindío (CGQ). This process is conducted in the following phases: planning: it is in which customer knowledge is performed and establish the list of activities to do. In the second phase; the execution, It performed the established activities, , which consist for the lines of Management of results, accounting, Budgeting and contractual; with the basis of information given by each control point through the Integrated Audit system (SIA) and Information system of visible Contracting (COVI). As a result of this process, we identified some inconsistencies, which, not being supported, explained or justified were forced to be taken as findings; which are carried to the last phase, reporting in which is prepared the points of view which the content is the opinion about reasonableness of the financial statements and the evaluation of the administrative management Budgeting and contractual.